The Differentiated Learning Strategy in Implementation Merdeka Belajar Curriculum to Improve Students’ Learning Outcomes of English Lesson in Elementary School - liza hidayati; Iis Sujarwati (Institute of Computer Science (IOCS), 2023)
The Ministry of Education and Culture (KEMENDIKBUD) issued a Merdeka Belajar and applied the differentiated learning strategy in teaching and learning. This study investigated the effectiveness of the application of differentiated learning strategy improved student’s outcomes of English lessons in Elementary school students. The sample of this study is 20 students of phase B in Merdeka Belajar Curriculum as fourth- grade students in the Islamic elementary school of IQRA’ 2. This study used the quantitative approach, pre- experimental with one group pre-test and post-test design was used to see there was an improvement of student’ outcomes. The instrument used to collect the data were test for 20 students of phase B in Merdeka Belajar Curriculum as fourth- grade students in the Islamic elementary school of IQRA’ 2. The data was analysed using SPSS Statistic 20, the result showed that average deal after treatment of 93,5000 and 27,000 before treatment, the significant difference between pre-test and post-test. The findings revealed the differentiated learning strategy in the implementation Merdeka Belajar Curriculum improves students’ outcomes of English lessons. Therefore, in teaching and learning based on the Merdeka Belajar applied, this strategy can applicate in English lessons to increase students’ outcomes through the differentiated by content, process and product.